Positioning control of a one mass rotary system using NCTF controller - Mohd Nor, Rozilawati; Chong, Shin Horng (2013)
In this paper a practical control scheme is discussed for the positioning and tracking control of a one mass rotary system. The practical controller designed must have high speed performance, high accuracy, robust to disturbance and parameter variation and have high positioning response which always welcome to industry. Hence, a Nominal Characteristic Trajectory Control (NCTF) controller has been proposed to yield high motion control performance and high robustness. This controller does not require exact model and parameter identification which make it easy to design. Basically, NCTF controller consists of a simple structure comprising Nominal Characteristic Trajectory (NCT) and Proportional Integral (PI) Compensator. Apart from a Conventional NCTF controller, the NCTF controller also improves to Continuous Motion NCTF (CM-NCTF) controller. CM-NCTF controller has same design procedure as Conventional NCTF controller and it is able to produce a slightly better performance than the conventional one by producing slightly faster response and smooth tracking performance. To evaluate the controller performance, the Conventional NCTF controller and CM-NCTF controller, was compared to PID control through experiment.